(untitled) (Eurasian Research Bulletin, 2022)
The article shows the legal foundations and tasks of accounting and considers the main approaches to its automation and the introduction of information technologies to improve the efficiency of management functions of economic sectors. The features of informatization and computerization of accounting in modern economic conditions are studied. The most common computer programs in practice are disclosed and analysed